Role of Bangladesh betar in reducing risk arising from natural calamities : a case study in Maheshkhali upazila of Cox's Bazar district in Bangladeh - Islam, Md. Ariful (BRAC University, 2016)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2014.